A Critical Appraisal of Inclusions of “Bioethics in Laboratory Medicine” into the Existing Postgraduate Curriculum of Pathology, Microbiology and Biochemistry - Anjankar Ashish P1 , Ninave Sudhir2 , Mishra Gaurav V3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Laboratory physicians confront with ethical issues in routine practice, but still ethics does notdraw the importance it deserves. A critical appraisal of the existing postgraduate curriculum of Pathology,Microbiology and Biochemistry with reference to its Bioethical inclusions to their conformity with referenceto Bioethical principles applicable to profession as included in UNESCO Declaration is needed.Aim: To critically analyse the inclusions of “Bioethics in Laboratory Medicine” into the ExistingPostgraduate Curriculum of Pathology, Microbiology and Biochemistry with reference to Bioethicalprinciples incorporated in UNESCO DeclarationMaterial and Methods: It was a descriptive study for rapid review of literature for the purposes ofidentification and critical appraisal of bioethical considerations in Laboratory Medicine in existingGuidelines for Competency Based Postgraduate Training Programme for MD in Pathology, Microbiology,Biochemistry with reference to Bioethical principles included in UNESCO declaration specially thoseapplicable to profession and not propagation or advocacy.Observations and Results: Upon critical analysis and mapping of the competencies in the Guidelines forCompetency Based Postgraduate Training Programme for MD in Pathology, Microbiology, Biochemistrywith the principles in the UNESCO universal declaration, 16 competencies were identified as professionalethical inclusions. 19 Competencies suggested in regards to “Bioethics in Laboratory Medicine” forGuidelines for Competency Based Postgraduate Training Programme for MD In these subjects to makethem commensurate with UNESCO universal declarationConclusion: This has brought out subsequent omissions which need to be managed in order to makecompetencies in Existing PG curriculum of Pathology, Microbiology and Biochemistry comparable with theUNESCO universal declaration and therefore, make it better and standardised on global and internationallevel.